2011
DOI: 10.1111/j.1538-7836.2011.04533.x
|View full text |Cite
|
Sign up to set email alerts
|

Baseline imaging after therapy for unprovoked venous thromboembolism: a randomized controlled comparison of baseline imaging for diagnosis of suspected recurrence

Abstract: Summary.  Background: After a first unprovoked venous thromboembolism (VTE), many patients have residual pulmonary and/or lower limb vascular obstruction following completion of short‐term anticoagulation. Residual vascular obstruction may complicate the diagnosis of recurrent VTE. Whether baseline imaging, conducted after completion of anticoagulation, helps in interpreting diagnostic testing in patients who subsequently have suspected recurrent VTE is unknown. Study design: The REVERSE study is a cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 19 publications
(22 reference statements)
0
33
0
3
Order By: Relevance
“…However, differentiating between RVO and recurrent ipsilateral DVT can occasionally be challenging, and duplex imaging after completion of anticoagulation has been shown to improve the accuracy for diagnosis of VTE recurrence. In a large cohort study by Hamadah et al, 15 patients with a first unprovoked DVT received 5 to 7 months of OAC. There were 121 patients in whom VTE recurrence was suspected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, differentiating between RVO and recurrent ipsilateral DVT can occasionally be challenging, and duplex imaging after completion of anticoagulation has been shown to improve the accuracy for diagnosis of VTE recurrence. In a large cohort study by Hamadah et al, 15 patients with a first unprovoked DVT received 5 to 7 months of OAC. There were 121 patients in whom VTE recurrence was suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Testing for this purpose usually is performed when antithrombotic therapy is being discontinued. 15 The third potential role for surveillance imaging is to detect the presence of RVO as a marker for patients at elevated risk for VTE recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, lack of early recanalization (after 3 months) appears to be more strongly associated with the risk of recurrence (Tan et al 2011). Independent of assessing residual thrombus as a predictor for recurrence, it is useful to document size and extent of the thrombus before discontinuation of OAC, as this will greatly help to diagnose or exclude a recurrent DVT, if the patient presents with new symptoms, after OAC has been stopped (Hamadah et al 2011). …”
Section: D-dimer Levelsmentioning
confidence: 96%
“…Third, it has been suggested that residual thrombi after a first PE may complicate the interpretation of imaging tests in case of clinically suspected recurrent PE. Therefore, assessment of the presence of residual thrombi after completion of anticoagulant treatment was proposed to facilitate differentiation between residual and new thrombi in case of a clinically suspected recurrent PE 47 . While older studies reported a high prevalence of residual PE, 57% at 6 months after diagnosis of PE in a systematic review, recent studies have reported a high complete PE resolution rate of 84-…”
Section: Management Of Clinically Suspected Recurrent Dvtmentioning
confidence: 99%